Dielectric and ferroelectric properties of Pb(Fe1/2 Nb1/2)O3 modification on Pb(Zr0.52Ti0.48)O3 ceramics. Issue 187 (12th February 2018) - Phewphong, S.; Photankham, W.; Kongpimai, J.; Seetawan, T.; Yimnirun, R.; Thanachayanont, C.; Wattanasarn, H.
ABSTRACT: Lead-based relaxor ferroelectric materials surged a favorable interest owing to their remarkable dielectric properties. Ferroelectric materials are sensitive to temperature changes. Dielectric properties are known to decrease when the temperature is higher than the temperature of the maximum dielectric constant. The objective of this research is to study the phase transition which was investigated by XRD, microstructure by SEM, the chemical bonds of samples identified by FTIR and the temperature dependent dielectric constants and loss tangents investigated as functions of temperature and frequency of (1 – x)Pb(Zr0.52 Ti0.48 )O3 -xPb(Fe1/2 Nb1/2 )O3 when x = 0, 10, and 30 mol%. A phase transition from morphotropic phase boundary (MPB) to tetragonal phase was observed. Grain size increased with increasing PFN was in the range of 0.99 to 3.61 µm. The shoulder of 0.7PZT52/48-0.3 PFN tend to disappear, the maximum absorbance around 419 cm –1 in FTIR according to the harmonic oscillator. The dielectric dispersion increased slightly as well as the dielectric maximum temperature decreased while dielectric constant at room temperature increased when added-PFN into PZT52/48 indicating ferroelectric nature. Meanwhile, the d33 and kp initially increase for x = 0 to 0.1 then decrease with the increase of the PFN contents for x = 0.3 due to amount of exceeded Fe 3+ /Nb 5+ ion.